Exosomes Derived from Dendritic Cells Treated with Schistosoma japonicum Soluble Egg Antigen Attenuate DSS-Induced Colitis - Wang, Lifu; Yu, Zilong; Wan, Shuo; Wu, Feng; Chen, Wei; Zhang, Beibei; Lin, Datao; Liu, Jiahua; Xie, Hui; Sun, Xi; Wu, Zhongdao (Frontiers in Pharmacology, 2017)
Exosomes are 30–150 nm small membrane vesicles that are released into the extracellular medium via cells that function as a mode of intercellular communication. Dendritic cell (DC)-derived exosomes modulate immune responses and prevent the development of autoimmune diseases. Moreover, Schistosoma japonicum eggs show modulatory effects in a mouse model of colitis. Therefore, we hypothesized that exosomes derived from DCs treated with S. japonicum soluble eggs antigen (SEA; SEA-treated DC exosomes) would be useful for treating inflammatory bowel disease (IBD). Exosomes were purified from the supernatant of DCs treated or untreated with SEA and identified via transmission electron microscopy, western blotting and NanoSight. Acute colitis was induced via the administration of dextran sulfate sodium (DSS) in drinking water (5.0%, wt/vol). Treatment with exosomes was conducted via intraperitoneal injection (i.p.; 50 μg per mouse) from day 0 to day 6. Clinical scores were calculated based on weight loss, stool type, and bleeding. Colon length was measured as an indirect marker of inflammation, and colon macroscopic characteristics were determined. Body weight loss and the disease activity index of DSS-induced colitis mice decreased significantly following treatment with SEA-treated DC exosomes. Moreover, the colon lengths of SEA-treated DC exosomes treated colitis mice improved, and their mean colon macroscopic scores decreased. In addition, histologic examinations and histological scores showed that SEA-treated DC exosomes prevented colon damage in acute DSS-induced colitis mice. These results indicate that SEA-treated DC exosomes attenuate the severity of acute DSS-induced colitis mice more effectively than DC exosomes. The current work suggests that SEA-treated DC exosomes may be useful as a new approach to treat IBD.